2016
DOI: 10.4172/2161-1041.1000172
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and the Impact of Geographical Location on the Relationships Between Phoenix dactylifera L. Germplasms Grown in Saudi Arabia

Abstract: Phoenix dactylifera L. is an important crop in the Middle East and North Africa. Date palm diversity faces risks including salinity and lack of rain. It is important to understand the genetic diversity of these germplasms. The objectives of this study were to investigate the degree of dissimilarity and to examine the impact of location on the genetic relationship between local cultivars in Saudi Arabia. The current study included 91 famous date palm accessions and a group of non-famous cultivars, collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…Generally, the structure result had shown shared ancestry between unknown date palm genotypes and known date palm cultivars that were early introduced. The admixture result of the present study at K = 3 is in agreement with those reported by [ 39 , 40 , 43 ]. Similarly, [ 44 ] revealed three differentiated date palm memberships at K = 3 using different SSR as well as four date palm groups at K = 4 using SNPs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Generally, the structure result had shown shared ancestry between unknown date palm genotypes and known date palm cultivars that were early introduced. The admixture result of the present study at K = 3 is in agreement with those reported by [ 39 , 40 , 43 ]. Similarly, [ 44 ] revealed three differentiated date palm memberships at K = 3 using different SSR as well as four date palm groups at K = 4 using SNPs.…”
Section: Discussionsupporting
confidence: 93%
“…This result was also supported with results in PCoA and population STRUCTURE analysis (i.e., intermixing distributions of genotypes on principal component axis and admixture structures were observed). The present result of PCoA showed certain match with the previous studies reported by [24,41], contrary to the report by [38][39][40]42]. According to the model-based clustering for genetic structure of date palm individuals, three genetically distinctive subpopulations were presented that were not formed in line with their collection places.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Among the nine sugar palm populations in this study, the populations of Lebak, Tasikmalaya, and Brebes had low heterozygosity based on Ho values that were smaller than the values (Table 2). Long-term crossing with individuals from outside the population and the process of adaptation to the environment can affect heterozygosity levels (Aljuhani 2016). In the populations of Lebak, Tasikmalaya, and Brebes, it is suspected that the incidence rate of crossings with individuals from outside the population is shallow, and environmental changes have not very successfully stimulated the response of significant adaptations of individuals in the population, thus not giving rise to new alleles.…”
Section: Genetic Diversity Of Populationsmentioning
confidence: 99%